Morfologi Jenis Tembelekan (Lantana camara L.) di Beberapa Wilayah Kepulauan Buton - Jumiati Jumiati; S. Hafidhawati Andarias (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2020)
Tembelekan (Lantana camara L.) is an upright or semi-climbing shrub with a distinctive odor which is native to tropical and sub-tropical regions. This plant has many variations. The purpose of this study was to determine the morphological diversity of tembelekan using field observation methods in Buton, Central Buton, and South Buton Districts. The characterization process was carried out at the Integrated Laboratory of the Muhammadiyah University of Buton. The results of the observations were analyzed qualitatively by comparing the characters between individuals. The results showed that there were two groups of tembelekan in the Buton Islands, namely the orange and pink flowering groups. The orange flowering group has ovate leaf shape, coarse-hairy leaf surface, acute leaf apice, acuminate leaf base, serrate leaf margin, longer leaf size than the pink group, sepal is almost identical in size, orange flower group has fewer corolla than pink flower group. While the pink flowering group has deltoid leaf shape, coarse-hairy leaf surface, acuminate leaf tip, acuminate leaf base, serrated leaf margin, different sepal sizes and magenta flower color. It can be concluded that the two groups of tembelekan have differences in leaf shape, leaf tip, leaf length, sepal size, number and color of the corolla.